02-23التنظيم القانوني للحق النقابي - وفقا للقانون - بوزيدي نجيب الله- بوزيدي يحي (جامعة محمد بوضياف المسيلة, 2025)
This study examines the legal framework governing the right to trade unionism in Algeria under Law No. 23-02 of April 25, 2023, which relates to the exercise of trade union rights. This legislation represents a significant reform milestone in the process of consolidating trade union freedoms and strengthening workers’ collective rights, in line with Algeria’s international commitments, particularly those stemming from the conventions of the International Organization. The research focuses on the general framework established by Law 23-02, especially regarding the freedom to form and join trade unions, the independence of trade union activity from public authorities and employers, as well as the legal requirements for the formation of trade union organizations and the scope of their activities.
Keywords: Trade union rights; Unions; Trade union organization